STUDIES IN HELIODORUS - RICHARD HUNTER (CAMBRIDGE PHILOLOGICAL SO, 2020)
Nine essays on Heliodorus' Aithiopika, assessing narrative technique, the construction of culture and the work's reception by more recent cultures.